2021
DOI: 10.1186/s12911-021-01700-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of central venous catheter-associated deep venous thrombosis in pediatric critical care settings

Abstract: Background An increase in the incidence of central venous catheter (CVC)-associated deep venous thrombosis (CADVT) has been reported in pediatric patients over the past decade. At the same time, current screening guidelines for venous thromboembolism risk have low sensitivity for CADVT in hospitalized children. This study utilized a multimodal deep learning model to predict CADVT before it occurs. Methods Children who were admitted to intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Jaffray et al [15 ▪▪ ] utilized traditional statistics methods to develop their model from the CHAT Registry, which had good discriminatory accuracy with an area under the receiver operating curve (AUROC) of 0.79 [95% confidence interval (CI) 0.73–0.84]. Badheka et al [5 ▪ ] and Li et al [7 ▪ ] both utilized neural networks to create models for CADVT. These had similar accuracy to the Jaffray et al model with an AUROC of 0.73 and 0.82, respectively.…”
Section: Risk Factors For Central Venous Catheter-associated Deep Vei...mentioning
confidence: 99%
See 1 more Smart Citation
“…Jaffray et al [15 ▪▪ ] utilized traditional statistics methods to develop their model from the CHAT Registry, which had good discriminatory accuracy with an area under the receiver operating curve (AUROC) of 0.79 [95% confidence interval (CI) 0.73–0.84]. Badheka et al [5 ▪ ] and Li et al [7 ▪ ] both utilized neural networks to create models for CADVT. These had similar accuracy to the Jaffray et al model with an AUROC of 0.73 and 0.82, respectively.…”
Section: Risk Factors For Central Venous Catheter-associated Deep Vei...mentioning
confidence: 99%
“…Central venous catheter (CVC) placement and ICU admission are the two most important risk factors for VTE in children [2]. Critically ill children are reported to develop CVC-associated DVT (CADVT) at rates of 2–39%, depending on the presence of symptoms and screening techniques [3,4,5 ▪ ,6,7 ▪ ]. CADVT can lead to pulmonary embolism, potentially prolonging duration of mechanical ventilation [8].…”
Section: Introductionmentioning
confidence: 99%
“…A feared complication following CVC placement is catheter‐associated deep vein thrombosis (CADVT) which is associated with increased morbidity and mortality in pediatric patients 7 . Several studies have reported that CADVT occurs in approximately 15%–39% of pediatric patients with a CVC and the risk is particularly high in preterm infants and neonates 9,10 . It must be noted, that the inflammatory and immunosuppressive effects of cardiopulmonary bypass and major surgery may have a different impact on the occurrence of complications in such patients when compared with other conditions 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Several studies have reported that CADVT occurs in approximately 15%-39% of pediatric patients with a CVC and the risk is particularly high in preterm infants and neonates. 9,10 It must be noted, that the inflammatory and immunosuppressive effects of cardiopulmonary bypass and major surgery may have a different impact on the occurrence of complications in such patients when compared with other conditions. 5,6 Furthermore, the question of the influence of the puncture site of a CVC on the development of CADVT for pediatric cardiac surgery patients has not been conclusively answered in studies.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies focused on defining risk factors for CADVT have been retrospective in nature. However, Li et al (10) have recently published an algorithm using machine learning that they have shown to predict the development of CADVT 72 hours in advance of the event. If this algorithm holds up to additional real-world experience, maybe we will find ourselves in the position where we can more precisely identify risk and likelihood of developing CADVT and therefore be able to prospectively address the question of treatment strategy.…”
mentioning
confidence: 99%